AUTHORITY OF THE CONSTITUTIONAL COURT TO ADJUDGE STATE ADMINISTRATIVE CASES - Abdul Ukas Marzuki (Adisam Publisher, 2025)
Court The Constitution (MK) is institutions that have authority main in interpret The 1945 Constitution (UUD), as set up in Article 24C of the 1945 Constitution and the Law Number 24 of 2003 concerning Court Constitution . However , in In practice , the Constitutional Court often handles related matters with State Administration (TUN), although in a way normative authority the is at in realm State Administrative Court (PTUN) in accordance with with Constitution Number 5 of 1986 concerning PTUN and its amendments. Research This aiming For analyze To what extent does the Constitutional Court have authority in to judge TUN matters and implications the law to system justice in Indonesia. Study This use method legal normative with approach regulation statute approach, approach case approach, and case study approach conceptual (conceptual approach). Data obtained from source primary law in the form of regulation legislation and Constitutional Court decisions , as well as source law secondary like literature law and journal academic. Research result show that there is overlap overlap authority between the Constitutional Court and the Administrative Court in a number of related cases with decision state officials , disputes results elections , as well as testing of legal norms that have an impact on state administration . This is cause uncertainty law and potential weaken principle separation power in system Indonesian justice . Therefore that , it is necessary existence revision to Constitution Court Constitution For clarify the limits of his authority so as not to enter realm law state Administration.